Tradisi Akademik Sekolah Dasar Unggulan di SDI Surya Buana Malang - Dwi Hasanah, Kartini; Barizi, Ahmad; Mubaraq, Zulfi; Susilawati, Samsul (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
The study of academic traditions in superior elementary schools, especially SDI Surya Buana Malang, is very important to study in more depth. This is because these studies never stop being debated. The aim of this article is to understand 3 things: First, the school's academic tradition paradigm. Second, internal and external factors that influence the school's academic traditions. Third, the positive implications of academic traditions for students at the school. The methods used were observation, interviews and documentation with a content analysis approach and were strengthened by literature review. The results found 3 things: first, the academic tradition paradigm has 3 forms: (1) instilling Islamic values ​​and philanthropy (2) integrative learning, PAI, and full day school (3) Strengthening Character Education (P3K) and religious culture programs. Second, internally, there are 3 factors that influence the academic tradition at SDI: (1) the leadership role of school principals and PAI teachers (2) the PJBL learning model (3) work motivation. Externally, there are 3 factors that influence the academic traditions at the school: (1) study tours (2) virtual tours (3) collaborative relationships with parents. Third, there are 3 positive implications of academic traditions for students: (1) improving the quality of institutions (2) student academic achievement (3) winning national and international. The conclusion of this article shows that SDI Surya Buana has an academic tradition as a superior Islamic elementary school